Periodontal connection with intestinal inflammation: Microbiological and immunological mechanisms. Issue 1 (4th March 2022) - Kitamoto, Sho; Kamada, Nobuhiko
Abstract: Humans have coevolved with the trillions of resident microbes that populate every nook and cranny of the body. At each site, the resident microbiota creates a unique ecosystem specialized to its environment, benefiting the development and maintenance of human physiology through harmonious symbiotic relationships with the host. However, when the resident microbiota is perturbed, significant complications may arise with disastrous consequences that affect the local and distant ecosystems. In this context, periodontal disease results in inflammation beyond the oral cavity, such as in the gastrointestinal tract. Accumulating evidence indicates that potentially harmful oral resident bacteria (referred to as pathobionts) and pathogenic immune cells in the oral mucosa can migrate to the lower gastrointestinal tract and contribute to intestinal inflammation. We will review the most recent advances concerning the periodontal connection with intestinal inflammation from microbiological and immunological perspectives. Potential therapeutic approaches that target the connection between the mouth and the gut to treat gastrointestinal diseases, such as inflammatory bowel disease, will be examined. Deciphering the complex interplay between microbes and immunity along the mouth–gut axis will provide a better understanding of the pathogenesis of both oral and gut pathologies and present therapeutic opportunities.